RETRACTED : The Influence of Website Quality, Price Perception and Sales Promotion on Shopee Consumer Satisfaction in South Jakarta - Choirunisya Putri Fauzi; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
This research aims to analyze how big the influence of variable website quality, price perception and sales promotion is towards consumer satisfaction of Shopee in South Jakarta. The research of using primary data obtained from the deployment of as many as 100 people questionnaire the Consumer Agency's logistics Feats Rides with multiple linear regression Methods are processed using the software SPSS version 23.0. The results showed that the quality of the website, the perception of price and sales promotion simultaneously had a positive and significant effect on customer satisfaction.